Answer:
Step-by-step explanation:
P(x) = (x + 3)Q(x) + R
<span> P(-3) = (0)Q(x) + R </span>
<span>i P(-3) = R </span>
<span>Now, P(-3) = (-3)⁴ - 9(-3)³ - 5(-3)² - 3(-3) + 4
</span>So
<span>P(-3) = 81 + 243 - 45 + 9 + 4 </span>
<span>=. 292
hope it helps</span>
Answer:
We know that a^2+b^2=c^2. The 45° angle lets us know that y=x (45+45+90=180), so the problem is y^2+x^2=4sqrt of 2
So you get y^2+x^2=32, and from there, since we know x and y are equal, you can just divide 32 by 2 then take the square root of that, so the answer should be <em><u>4</u></em><em><u> </u></em><em><u>for</u></em><em><u> </u></em><em><u>both</u></em><em><u> </u></em><em><u>x</u></em><em><u> </u></em><em><u>and</u></em><em><u> </u></em><em><u>y</u></em>
Step-by-step explanation:
let me know if I'm wrong lol